20 Situated cognition 360° editor 2021: a solution for interactive medical training during the COVID-19 pandemic period. (15th December 2021) - Ding, Zixuan; Wang, Min; Chen, Szu-Han; Kidd, Fergus; Molyneux, Gemma; Conner, Sue; Taylor, Andrew; Sebire, Neil J; Mohamedally, Dean; Visram, Sheena
Abstract : Introduction: Imagine entering an operating theatre or developing clinical skills in empathy and communication through Virtual Reality. To enhance the experience of learning, novel methods using VR have been researched and simulated for clinicians. This is because some aspects of clinical training, like conducting procedures and effective team communication focus on 'learning by doing' which is difficult to recreate remotely. Here we present a proof-of-concept prototype of a 360°-video editor that augments 360° videos with media to create a mixed reality learning experience. Method: An editor was built inside Unity to augment 360°-videos of real-world scenarios in healthcare with interactive data. Unity is a cross-platform games engine used to create two-dimension, three-dimension, virtual reality, and augmented reality games, as well as video players to play panoramic 360°-videos. The video player is attached to a Render Texture and a Skybox material that provides the spherical surface for the 360°-video achieving an immersive experience. Results: The editor comprises two software packages, one for the trainer, another for the learner. As a unique feature, we introduce clickable Hotspots. This enables users to annotate the 360° film by tagging specific artefacts in the environment and create a place-based interaction. These Hotspots are anchored to a position and can display text and images, and form part of a novel branched timeline of nested data. The intention being the trainer would create the film and annotate the environment with interactive media. This would then be available to the learner, who would use the player to view a bespoke teaching package. Conclusion: Situated Cognition 360 Editor 2021 envisages trainers creating interactive 360°-video learning experiences using real life scenarios in healthcare. Future steps involve user experience evaluations, co-design and development of new learner interactions that deliver low cost, remote and easily deployed healthcare education through immersive learning environments.